Genetic and phenotypic trends for growth traits of buffaloes in Brazil - Malhado, Carlos Henrique Mendes; Ramos, Alcides Amorim [UNESP]; Carneiro, Paulo Luiz Souza; Souza, Julio César de; Lamberson, William R. (Pagepress Publ, 2007)
The objectives this paper were to estimate genetic parameters and genetic and phenotypic trends of birth weight (BWT) and weights adjusted to 205 (WT205), 365 (WT365) and 550 (P550) days of age of beef buffaloes born from 1985 to 2003 in Brazil. For BWT and WT205 the model included direct and maternal genetic and maternal environment as random effects and contemporary and genetic groups as fixed effects. For WT365 and WT550 the same model was used except without direct maternal and maternal environmental effects. The genetic and phenotypic trends were estimated by regression of means of dependent variables on birth year of animals Regressions were obtained by using two methodologies: 1) linear regression; and 2) non-parametric splined regression. The direct heritability estimates were 0.09, 0.45, 0.46 and 0.58 for BWT, WT205, WT365 and WT550, respectively. The direct genetic trends from linear regression were 0.01, 0.23, 0.58 and 1.40 kg per year for PN, WT205, VVT365 and WT550, respectively (P<0.001 for all). Phenotypic trends were strongly positive while genetic trends were consistently positive but small. Genetic parameters indicate potential for increased rate of genetic change with full implementation of genetic improvement programs.
Keywords: Buffalo; Genetic trend; Genetic parameters; Heritability